ISLAMIC FINANCE AND SUSTAINABILITY NEXUS: SUKUK AND FINANCIAL INCLUSION IMPACTS ON RENEWABLE ENERGY, CO2 AND LIFE-EXPECTANCY - Danial Muhammad Wirdyansyah; Ananda Maulana Gilbarani; Neneng Hartati; Widiawati Widiawati; Khemal Youwangka (Universitas Airlangga, 2026)
This study examines the impact of sukuk and Islamic financial inclusion on sustainability outcomes across 14 OIC countries from 2013 to 2024 using a quantitative research framework employing Fixed Effects Model (FEM), Random Effects Model (REM), Quantile Regression (QREG), and Fully Modified Ordinary Least Squares (FMOLS). The findings reveal that sukuk significantly promotes renewable energy consumption and life expectancy, confirming its role as a financing tool for clean infrastructure and welfare projects. However, its effect on reducing carbon intensity is weak and context-dependent. Islamic financial inclusion demonstrates a positive association with renewable energy but yields mixed effects on carbon intensity and health outcomes, reflecting its dependence on institutional and socioeconomic factors. Robustness checks with 2000 bootstrap replications corroborate these results, confirming the significant positive impact of sukuk on renewable energy and revealing a significant negative influence of both sukuk and financial inclusion on carbon intensity after accounting for sampling variability. The study concludes that sukuk and Islamic financial inclusion serve as dual transmission channels for sustainability, with policy implications for expanding green sukuk frameworks and integrating financial inclusion with institutional reforms.